Lípidos cerebrales en cobayos de las grandes alturas - Fernández V., Alberto (2000)
Body weight, brain weight, and total fat, cholesterol, phospholipids and sphingolipids (sphingomyelines, cerebrosides, sulfatides, gangliosides) in brain were determined in 20 male guinea pigs, 10 native from sea-level zones (Lima, 150 m) and 10 from high altitude (Cerro de Pasco, 4380 m). The difference in body weight was significant, the high altitude guinea pig weight being reduced in 13.8% (p < 0.05). Neither brain weight nor total brain fat content showed significant differences. High altitude animals showed significant reductions: of cholesterol, 12.6% (p <0.01); of total phospholipids, 4,6 %; oj cerebrosides, 10.6% (p<0.001); and of sulfatides, 14.1% (p<0.001). The plasmalogens were increased in 22,6% (p<0.005). There were no significant differences in sphingomyelin and ganglioside levels. The differences found suggest that chronic exposure to high altitude hypoxia might alter composition of brain lipids, particularly those constituing the myelin sheath.